An in vitro exploratory study of dietary strategies based on polyphenol-rich beverages, fruit juices and oils to control trimethylamine production in the colon. Issue 12 (22nd November 2018) - Bresciani, Letizia; Dall'Asta, Margherita; Favari, Claudia; Calani, Luca; Del Rio, Daniele; Brighenti, Furio
Abstract : Dietary choline andl -carnitine are biotransformed by the fecal microbiota into TMA, the intestinal precursor of TMAO, and its formation could be influenced by (poly)phenol-rich foods. Abstract : Trimethylamine- N -oxide (TMAO) has been described as a new biomarker of cardiovascular disease (CVD), derived from gut microbial biotransformation of dietary choline andl -carnitine into trimethylamine (TMA) and subsequent hepatic oxidation. (Poly)phenols are among the dietary factors able to interfere with microbial enzymatic activity, possibly modulating TMA biotransformation at the gut level. The aim of this work was to investigate the in vitro biotransformation of choline and carnitine using faecal starters obtained from omnivorous and vegetarian subjects and the effect of (poly)phenol-rich foods on TMA production. Choline andl -carnitine were fermented with vegetarian or omnivorous faecal slurries, alone or in combination with 10 (poly)phenol-rich food items. TMA production from carnitine, but not from choline, was significantly lower when vegetarian faecal starters were used and, among the tested food items, blonde orange juice significantly reduced TMA formation during faecal biotransformation. Consequently, the main compounds of orange juice, namely phenolic compounds, terpenes, limonoids, organic acids and sugars, were tested individually. Sugars exerted the highest inhibitory effect on TMA production. Despite some limitations deriving from the applied in vitro model, this is the first work describing a possible role of some (poly)phenol-rich dietary products on the modulation of TMA colonic production. Free sugars were the main factor responsible for TMA inhibition, suggesting a potential beneficial role of colonic fermentation of carbohydrates in reducing TMA formation from its precursor molecules. This work opens new research directions to evaluate the effect of dietary fermentable fibre on TMA production and, potentially, on circulating TMAO levels.